Analisis Pengaruh Penerapan Tri Hita Karana terhadap Tingkat Kepuasan Wisatawan di Kawasan Agrowisata Ceking, Kecamatan Tegallalang, Kabupaten Gianyar - Puspitadewi, I Dewa Ayu; Windia, Wayan; Sri Astiti, Ni Wayan (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management); Vol 3 No 1 (2015): Vol. 3 - No. 1 - Mei 2015)
The Tri Hita Karana application concept is universal and very relevant for agricultural development concept. Tri Hita Karana consist of three subsystems, there are parhyangan, pawongan, and palemahan. Three of these subsystems have interrelated to built a tourist has appeal and increase the satisfaction value for tourists caused they are able to maintain harmony and sustainability of Agrotourism business. It can also avoid land conversion caused by an increase in tourist arrivals, therefore it can avoid conflicts and frictions that occur in the community. Related to that, this research aims to   (1) discover tourist responds of the application of the Tri Hita Karana in the Ceking Agrotourism Region; (2) discover tourist satisfaction in the Ceking Agrotourism Region; and (3) analyze the Tri Hita Karana application effect for tourist satisfaction level simultaneously and partially in the Ceking Agrotourism Region The samples in this study using the accidental sampling technique there were 40 respondents consisting of domestic and foreign tourists over the age of 17 years old who doing a search in the area of Agro Ceking terracing area. Data were collected using distributed questionnaires to tourists who visited the Ceking Agrotourism Region, then analyzed using multiple linear regression analysis by using SPSS 17.0 for windows. The results are (1) Tourists votes of the application of the Tri Hita Karana in the Ceking Agrotourism Region relatively good, it’s looked of the level of votes on the implementation tourists; (2) level of tourists satisfaction in the Ceking Agrotourism Region was high; (3) the Tri Hita Karana application effect for tourists satisfaction level simultaneously and partially in the Ceking Agrotourism Region was influential and significant. Based on this research, the managers are recommended to maintain and improve the application of the Tri Hita Karana by towards to developing an upgrade in Parhyangan spiritual activities object, which is worth contributing to farmers, therefore increased the tourism supporting facilities that safe and comfortable and not damage the environment
Keywords: tri hita karana, satisfaction, agrotourism, tourist.